"تأثير الحصويات البازلتية المحلية على سلوك العناصر الإنشائية المسلحة المعرضة للقص والانعطاف " - العيسى, رياض; سعود, أندرواس; محمد, علي (Latakia University Journal -Engineering Sciences Series, 2018)
تبحث هذه الورقة دراسة عملية مخبرية لإمكانية الاستفادة من مورد هام من الموارد الطبيعية المتوفرة في القطر، وهو البازلت المتواجد بكميات كبيرة في المنطقة الجنوبية (السويداء)، لبيان مدى تحقيقه لمتطلبات المواصفات القياسية لاستعماله في تصنيع الخرسانة وذلك من خلال اختبار خمس خلطات تصميمية للبيتون المكعبية منها بأبعاد (15*15*15) سم و اسطوانية بأبعاد (15*30) سم وبنسب مختلفة للحصويات البازلتية والكلسية الدولوميتية المستخدمة فيها كالتالي (0% بازلت و100% كلس)، (25% بازلت و75% كلس)، (50% بازلت و50% كلس)، (75% بازلت و25% كلس)، (100% بازلت و0% كلس) على مقاومة الضغط والشد بالانفلاق ومعامل المرونة بأعمار (28-7-3) يوم، وتأثيره على سلوك العناصر الإنشائية المسلحة المعرضة للقص والانعطاف من خلال اختبار جوائز بيتونية مسلحة بأبعاد cm (16 X 12 X 200) على القص والانعطاف ومعامل التشقق بأعمار (14-28) يوم. وفي النتيجة تبين ما يلي: أنه باستعمال الحصويات البازلتية بنسبة 100% ازدادت مقاومة الانعطاف للجوائز البيتونية المسلحة بنسبة 20% تقريباُ. كما نلاحظ أنه عند عمر 14 يوم كانت مقاومة الانعطاف للجوائز البيتونية المسلحة المصبوبة باستخدام خلطات بيتونية فيها نسبة الحصويات البازلتية 100% كانت أعلى من مقاومة الانعطاف للجوائز البيتونية المصنعة باستخدام حصويات كلسية بنسبة 100%. وبينت الدراسة أنه باستعمال الحصويات البازلتية بنسبة 100% ازدادت مقاومة القص للجوائز البيتونية المسلحة بنسبة 20% تقريباُ. كما نلاحظ أنه عند عمر 14 يوم كانت مقاومة القص للجوائز البيتونية المسلحة المصبوبة باستخدام خلطات بيتونية فيها نسبة الحصويات البازلتية 100% كانت أعلى من مقاومة القص للجوائز البيتونية المصنعة باستخدام الخلطة المرجعية. كما تبين أن عتبة اللدونة للجوائز المصبوبة باستخدام حصويات كلسية كانت أعلى من الجوائز المصبوبة باستخدام حصويات بازلتية وهذا يدل على أن الحصويات البازلتية أعطت قساوة أعلى للجوائز البيتونية المسلحة. This paper studies a practical laboratory process of the possibility of benefiting from an important resource of the natural resources available in the country, namely "Basalt" which is found in large quantities in the southern region (As-Suwayda) to demonstrate how much it meets the requirements of Standard Specifications for use in the manufacture of concrete by testing five design mixtures of concrete , of which the cubic dimensions are (15% x 15) cm and the cylindrical dimensions are (15 * 30 cm) with different percentages of the basaltic and dolomitic calcareous compounds used in them as follows: (0% basalt and 100% lime),( 25% basalt and 75% lime) , (50 % basalt 50 % lime) (75% basalt 25% lime), (100%basalt and 0% lime) on the strength of pressure and tensile strain by Splitting and Moduls of Elasticity of ages (28-7-3) days, and its effect on the behavior of Reinforced Structural Elements susceptible to shear and Bending through testing Reinforced beams of dimensions (16 × 12 × 200) cm on shear, Bending and cracking Moduls (Coefficient) with ages of (14-28) days. As a result it was found that : By using basalt stones at a percentage of 100 % , Bending Strength of the reinforced concrete beams increased by approximately 20%. We also note that at the age of 14 days, Bending Strength of the reinforced concrete beams cast using concrete mixtures with 100% basalt stones was higher than the Bending strength of concrete beams made by using calcite stones at a percentage of 100% The study also showed that by using basalt stones at a percentage of 100 % , Shear Strength of the reinforced concrete beams increased by 20% approximately. We also note that at the age of 14 days, Shear Strength of the reinforced concrete beams cast using concrete mixtures with 100% basalt stones was higher than the shear strength of concrete beams made by using concrete referential Mix. It was also found that the plasticity threshold for beams cast using calcareous stones was higher than the beams cast using basalt stones. This indicates that basaltic stones gave higher severity to the reinforced concrete beams.